IHH enhancer variant within neighboring NHEJ1 intron causes microphthalmia anophthalmia and coloboma - Ohad Wormser; Yonatan Perez; Vadim Dolgin; Bahman Kamali; Jared A. Tangeman; Libe Gradstein; Yuval Yogev; Noam Hadar; Ofek Freund; Max Drabkin; Daniel Halperin; Inbar Irron; et al. (npj Genomic Medicine, 2023)
Abstract Genomic sequences residing within introns of few genes have been shown to act as enhancers affecting expression of neighboring genes. We studied an autosomal recessive phenotypic continuum of microphthalmia, anophthalmia and ocular coloboma, with no apparent coding-region disease-causing mutation. Homozygosity mapping of several affected Jewish Iranian families, combined with whole genome sequence analysis, identified a 0.5 Mb disease-associated chromosome 2q35 locus (maximal LOD score 6.8) harboring an intronic founder variant in NHEJ1, not predicted to affect NHEJ1. The human NHEJ1 intronic variant lies within a known specifically limb-development enhancer of a neighboring gene, Indian hedgehog (Ihh), known to be involved in eye development in mice and chickens. Through mouse and chicken molecular development studies, we demonstrated that this variant is within an Ihh enhancer that drives gene expression in the developing eye and that the identified variant affects this eye-specific enhancer activity. We thus delineate an Ihh enhancer active in mammalian eye development whose variant causes human microphthalmia, anophthalmia and ocular coloboma. The findings highlight disease causation by an intronic variant affecting the expression of a neighboring gene, delineating molecular pathways of eye development.